Moral Injury Among Frontline Long-Term Care Staff and Management During the COVID-19 Pandemic - Reynolds, Kristin A.; Pankratz, Lily; Jain, Barbie; Grocott, Bronwen; Bonin, Lynette; King, Gillian; Sommer, Jordana L.; El-Gabalawy, Renée; Giuliano, Ryan J.; Kredentser, Maia; Mota, Natalie; Roos, Leslie E. (Frontiers in Health Services, 2022)
Background A growing body of research highlights the experiences of moral injury among healthcare professionals during the COVID-19 pandemic. Moral injury (i.e., participating in or witnessing acts that violate one's central moral values), is associated with a host of psychological sequelae and corresponding negative psychosocial impacts. There is a lack of research examining the experiences of moral injury among those working in long-term care settings during the COVID-19 pandemic. Given the drastic impact that the COVID-19 pandemic has had on long-term care facilities in Canada, it is important to understand the experiences of moral injury among those working in long-term care settings to inform the development of effective prevention and intervention strategies. Objectives & Method The objectives of this study were to understand the experiences and impact of moral injury among Canadian frontline long-term care workers (staff and management) during the COVID-19 pandemic. Participants (N = 32 long-term care staff and management working in Ottawa and Manitoba) completed in-depth, semi-structured qualitative interviews and clinical diagnostic assessments (Mini International Neuropsychiatric Interviews; MINI; Version 7.0.2) between March 2021-June 2021. Findings The core category of our qualitative grounded theory model of moral injury in long-term care exemplified four shared types of morally injurious experiences, paired with cognitive, affective, and physiological symptom domains. Seven associated main themes emerged, contributing to the experiences and impact of moral injury in long-term care: 1) Beliefs about older adults and long-term care; 2) Interpretation of morally injurious experiences; 3) Management of morally injurious experiences; 4) Long-term care pandemic impacts; 5) Personal pandemic impacts; 6) Structural impacts in long-term care; and 7) Mental health needs and supports. Clinical assessments demonstrated anxiety disorders (n = 4) and feeding and eating disorders (n = 3) were among the most frequently classified current psychiatric disorders among long-term care workers. Conclusions This is the first Canadian study to examine the experiences and impact of moral injury in long-term care during the COVID-19 pandemic using qualitative and clinical diagnostic methodologies. Implications and insights for screening and intervention are offered.